2016
DOI: 10.4209/aaqr.2015.12.0670
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Robotic Weighing System and Quality Practices for Gravimetric Mass Measurements

Abstract: Gravimetric analysis is an essential baseline measurement for air quality monitoring networks to monitor particulate matter and to track adherence to the National Ambient Air Quality Standards. The Clean Air Act requires the state and local agencies to monitor and report particulate matter concentrations as a part of their air monitoring requirements. Highthroughput gravimetry laboratories need to be capable of weighing thousands of filter-based samples each month while maintaining strict quality control requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The arm movements were closely monitored using the weighing results. Our results showed that the RWS showed a high degree of precision and accuracy with no significant drift and with negligible effect of static electricity, and imparted no contamination onto the filters (Presler-Jur et al, 2016).…”
Section: Project Analysis Techniquesmentioning
confidence: 67%
See 3 more Smart Citations
“…The arm movements were closely monitored using the weighing results. Our results showed that the RWS showed a high degree of precision and accuracy with no significant drift and with negligible effect of static electricity, and imparted no contamination onto the filters (Presler-Jur et al, 2016).…”
Section: Project Analysis Techniquesmentioning
confidence: 67%
“…Being able to estimate BC from Teflon filters thus enhances the ability to expand the spatial scale of estimated EC measurements at a lower cost than thermal OC/EC analysis, if, for example, it is performed routinely on these network filters. The ability to automate such measurements on Teflon filters using a robotic weighing system (RWS) (Presler-Jur et al, 2016) while also measuring gravimetric mass provides exceptional value by generating concurrent BC data at reduced human labor effort relative to multiple manual measurements. Further, the ability to analyze archived filters enables expanding the temporal extent of estimated EC data.…”
Section: And the National Park Service [Nps] Interagency Monitoring Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Automated weighing systems have been used in which filters are loaded into cassettes and robotically moved to and from the microbalance for automatic weighing (Presler-Jur et al 2016). While weights have been shown to be comparable to those derived from manual weighing, there is little technician time saved as the filters must be transferred from the Petri slide to the cassettes and back again.…”
Section: Filter Processing Facilitymentioning
confidence: 99%